ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH MERGER PADA SEKTOR PERBANKAN - Hikmah (LPPM Universitas Ibnu Sina, 2021)
This study aims to determine changes in the company's financial performance before and after the case merger in banking companies listed on the Indonesia Stock Exchange. The population in this study were all banking companies that carried out the merger. The sample used was five banking companies that conducted mergers in 2015 to 2019. The technique used in sampling was purposive sampling technique. The data analysis technique used in this research is quantitative analysis to test the differences in financial performance ratios with the Wilcoxon Signed Rank Test. The result have changes in banking companies listed on the Indonesia Stock Exchange between before and after the merger